Characteristic Features and Periodic Classification of the Medieval Armenian Historiography - Margaryan, Hayrapet (ՀՀ ԳԱԱ հրատ.)
The ways the specific features of the Armenian historiography have developed, the problems of exploring the specific features of different centuries and their periodization has not attracted too much attention by the researchers. Միջնադարյան հայ պատմագրության յուրահատկությունների, զարգացման ուղիների, տարբեր դարաշրջանների համար բնութագրական կողմերի խնդիրները, ավանդաբար, քիչ են գրավել հետազոտողների ուշադրությունը: Բաց է մնացել նաև հայ միջնադարյան պատմագրության պարբերացման հիմնահարցը:Проблемы особенностей средневековой армянской историографии, путей ее развития, характерных черт разных эпох традиционно мало привлекали внимание исследователей.
Keywords: Medieval History; History